BindingDB Entry 50038564: Usimines A-C, bioactive usnic acid derivatives from the Antarctic lichen Stereocaulon alpinum. - BindingDB (BindingDB, 2012)
Small molecule binding data for protein Protein-tyrosine phosphatase 1B, Uniprot P18031